L'educazione incorporata nel lavoro - Paolo Federighi (Firenze University Press, 2010)
The knowledge and educational values that are generated when you work are the subject of this essay. In particular, the focus is on the way while you work, the processes of acquisition / production of knowledge and behavior take place, and especially how to handle relative paths so intentionally by a person engaged in productive activities, as the company responsible for making the working environment. The aim is to learn how to reduce the opportunities for prediction of informal and not as a chance to increase production factors in different educational activities that produce specific processes of personal growth and professional workers.